Mechanical performance improvement for various 9Cr ODS alloys at room temperature and 650 °C by tailoring hot rolling and subsequent heat treatments - Ruhao Sun; Hao Li; Jie Xiong; Pengfei Wang; Zhenya Chen; Meini Yuan; Xiaosheng Zhou (Journal of Materials Research and Technology)
With respect to transformable 9Cr oxide dispersion strengthened (ODS) steels, the interaction between moving phase interface and oxide nanoparticles could lead to the inhomogeneous distribution of oxide particles. Nevertheless, the coupled effects between oxides and phase interface upon dynamic recrystallization still remains unclear. In this work, transformable 9Cr ODS alloys with different Ti and C additions were fabricated, hot-rolled with different reductions and then annealed. For each ODS alloy, dynamic recrystallization of austenite occurs upon hot-rolling, and the oxides in hot-rolled alloys are distributed in lines parallel to rolling direction. With the hot rolling reduction increasing, the line spacing of oxides is decreased, and alloy composition has negligible effects on oxide distribution compared to rolling reduction. A strong <110> fiber texture is dominated in each hot-rolled alloy, and with the deformation reduction increasing, the grain morphology changes from equiaxial to elongated ones. Both alloying composition and rolling reduction have significant effects on the mechanical performance of ODS alloys at room temperature and 650 °C. By optimizing the hot rolling and annealing treatment processes, the 9Cr ODS alloy with both Ti and C additions exhibits favorable strength and ductility at both room temperature and 650 °C.